Angsana Canopy Enterprise / Siti Sharina Md Salim... [et al.] - Md Salim, Siti Sharina; Seath, Siti Salwa; Mohamed Ariff, Siti Rahayu; Wan Kamardin, Wan Nazratul Syima; Md Noor, Azura (2000)
Angsana Canopy Enterprise provide a service of rental equipment for any events and ceremony. They also send the order to the respective place. Angsana Canopy Enterprise was a partnership business that been organized by five members. They run a business that in a concept of rental service equipment for an events and ceremony. This business was located at Alor Setar, Kedah and was run on 1st January 2002.